The Role of Organizational Culture in Shaping Employee Green Behavior: A Case Study at Google: JEL Classification: M14, M54, Q56, L86, O33 - Ardi Mahrifal; Awaluddin Awaluddin; Ilham Labbase; Achmad Gani (Newinera Publisher, 2026)
The escalating global environmental crisis has compelled organizations to integrate sustainability as a core strategic imperative rather than a peripheral corporate responsibility. This study examines how organizational culture shapes Employee Green Behavior (EGB) within knowledge-based industries, using Google (Alphabet Inc.) as a case study. Employing a qualitative literature review method, the research analyzes secondary data from environmental reports, academic journals, and prior studies to explore the interaction between green organizational culture, infrastructure, and employee behavior. The findings reveal that Google’s sustainability performance is not solely driven by technological efficiency such as achieving a Power Usage Effectiveness (PUE) of 1.10 and significant carbon-free energy adoption but is deeply rooted in its organizational culture. Through Schein’s three-layer cultural framework, the study demonstrates how tangible artifacts (biophilic office design and renewable energy infrastructure), espoused values (“moonshot” innovation), and underlying assumptions (technology as a solution for planetary sustainability) collectively foster voluntary, innovative, and consistent EGB. Employee initiatives such as the Green Googlers community, extensive carbon literacy training, and carbon-aware computing practices illustrate how sustainability becomes embedded in professional identity rather than enforced through rigid policies. The study concludes that the synergy between green infrastructure and cultural internalization enables resilience amid technological challenges, including rising AI-related emissions, and positions organizational culture as a critical driver of sustainable transformation in the digital economy.